Photodynamic therapy in a patient with hpv-associated lsil of the cervice (clinical case) - E. V. Filonenko; N. I. Grigoryevykh; A. D. Kaprin (Biomedical Photonics)
The article describes a clinical example of timely, safe and effective photodynamic therapy (PDT) in a patient diagnosed with human papillomavirus (HPV) CIN I-associated cervical cancer after ineffective vaccination with 4-valent Gardasil vaccine. Clinical case demonstrates the low effectiveness of HPV vaccination in patients with established HPV infection. In this patient, the lack of adequate treatment for about 1.5 years led to the development of HPV associated CIN I of the cervix. Center for Laser and Photodynamic Diagnostics and Therapy of Tumors and MRI P.A. Herzen, the patient underwent a course of antiviral PDT with the achievement of complete regression of dysplasia and complete eradication of HPV viruses. The patient tolerated the treatment well, without complications. The period of relapse-free follow-up is 19 months.